(untitled) (Research, Society and Development, 2020)
The goal of this paper was to evaluate the ways of contribution of the Thematic Unit (TU) “The Chemistry of Cleaning”, to approach subjects as molecular geometry, polarity, solubility and intermolecular forces in four classes of first year’s students of High School in a Public School from Porto Alegre. Thus, a TU was elaborate reasoned in a STS perspective, containing several didactic resources such as reading activities, experiments, physical model’s production and exercises put it into cleaning context. The data were collected with questionnaires applied with the students and with notes in the Field Diary. The result shows that the didactic material is flexible and presents a lot of potential to the Chemistry teach, in conceptual aspects and inciting the critical reflection about label analysis and conscious consumption of hygiene products.